Heat Flux at the Surface of Metal Foil Heater under Evaporating Sessile Droplets; International Journal of Aerospace Engineering; Vol. 2015 - Marchuk I. V. Igor Vladimirovich; Karchevsky A. L.; Surtaev A. S. Anton Sergeevich; Kabov O. A. Oleg Aleksandrovich (2015, 2015)
Title screen